2021
DOI: 10.1002/cnm.3430
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical model of the auditory nerve response to stimulation by a micro‐machined cochlea

Abstract: We report a novel mathematical model of an artificial auditory system consisting of a micro‐machined cochlea and the auditory nerve response it evokes. The modeled micro‐machined cochlea is one previously realized experimentally by mimicking functions of the cochlea [Shintaku et al, Sens. Actuat. 158 (2010) 183–192; Inaoka et al, Proc. Natl. Acad. Sci. USA 108 (2011) 18390–18395]. First, from the viewpoint of mechanical engineering, the frequency characteristics of a model device were experimentally investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(101 reference statements)
0
2
0
Order By: Relevance
“…It has been shown that PVDF-TrFE is more suitable for transducers than PVDF because the electromechanical coupling factor of PVDF-TrFE ( = 0.3 [ 34 ]) is higher than that of PVDF ( = 0.14 [ 35 ]), and the mechanical and dielectric loss tangent of PVDF-TrFE ( = 0.0335 and = 0.089 [ 36 ]) are lower than those of PVDF ( = 0.0789 and = 0.184 [ 36 ]). Three pairs of upper electrodes are used to obtain electrical signals based on biological tonotopy and control the oscillation through feedback control [ 10 , 17 , 18 , 29 ]. Because the electrodes are metallic and the piezoelectric film and elastic layer are organic materials, the adhesion of these materials is difficult.…”
Section: Theoretical and Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that PVDF-TrFE is more suitable for transducers than PVDF because the electromechanical coupling factor of PVDF-TrFE ( = 0.3 [ 34 ]) is higher than that of PVDF ( = 0.14 [ 35 ]), and the mechanical and dielectric loss tangent of PVDF-TrFE ( = 0.0335 and = 0.089 [ 36 ]) are lower than those of PVDF ( = 0.0789 and = 0.184 [ 36 ]). Three pairs of upper electrodes are used to obtain electrical signals based on biological tonotopy and control the oscillation through feedback control [ 10 , 17 , 18 , 29 ]. Because the electrodes are metallic and the piezoelectric film and elastic layer are organic materials, the adhesion of these materials is difficult.…”
Section: Theoretical and Experimental Methodsmentioning
confidence: 99%
“…However, two commonly known bottlenecks in the development of fully insertable cochlear implants are (1) the lack of power available to stimulate the nerve using biocompatible materials and (2) the difficulty of achieving a reproducible frequency range within the dimensions of the cochlea. We [ 17 , 18 , 29 ] and other groups [ 30 , 31 , 32 , 33 ] addressed the former issue by developing a nonlinear feedback control system that mimics the amplification of outer hair cells. However, there have been few studies of microdevices being implanted in the cochlea, and their performance, particularly in terms of mechanical dynamics, has yet to be thoroughly established.…”
Section: Introductionmentioning
confidence: 99%